PENINGKATAN KEAMANAN KOS-KOSAN DENGAN SISTEM PENDETEKSI TUBUH DAN WAJAH BERBASIS CLUSTERING - Maulana, Ahmad; Hidayatulloh, Syarif; latif, Abdul (Universitas Majalengka, 2024)
Boarding house security security is an important thing to pay attention to, considering the many cases of theft and sexual harassment that occur in these residences.theft and sexual harassment that occur in these residences.One way to improve the security of boarding houses is to use a body and face detection system.body and face detection system, this system helps to identify people who enter and exit the boarding house.who enter and exit the boarding house, so that at least it can help to prevent crime. One of the methods that can be used to build a body and face detection system is the clustering method, this clustering method can be used to group image or video data based on their similarities, in this case, the clustering method can be used to group images or videos of people entering and leaving the boarding house